Evaluasi Kualitas Kebergunaan, Kualitas Informasi, Dan Kualitas Interaksi Pelayanan Pada Website Dinas Pendidikan Menggunakan Metode Webqual Dan Importance Performance Analysis (Studi kasus : Website Dinas Pendidikan Kabupaten Pasuruan) - Rizki Widya Priyangga; Admaja Dwi Herlambang; Niken Hendrakusma Wardani (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
One of the problems in this research is the existence of the evaluation has not been done of Education department website. The purpose of the evaluation is conducted to find out the quality of usability, information quality, and service interaction quality of website in Education Department of Pasuruan Regency. The sample used of 100 respondents from a population of website users, with sampling simple random sampling. The collection of data obtained from the dissemination of the questionnaire then analyzed using descriptive statistics and calculation of Importance Performance Analysis (IPA). The results of descriptive statistics that the third variable included in the high category. The results of the value of the variable gap usability it of -0.35, information quality of-0.32, and service quality of interaction -0.36. Based on this website we can conclude that the website is considered able to meet the ideal quality. Indicators that need to be done improvements web colors, comfortable design is viewed, the type and size of the font is easy to read, the color of the background contrasts with the font color, information up to date, useful information for user information is beneficial to users, ease of communicating with organizations (links to the SKPD), and speed to respond and give a response.